Effect of temperature on Candida antartica lipase B activity in the kinetic resolution of acebutolol - Mariani Rajin; A H Kamaruddin (2016)
Thermodynamic studies of free Candida antartica lipase B in kinetic resolution of acebutolol have been carried out to characterize the temperature effects towards enzyme stability and activity. A decreased in reaction rate was observed in temperature above 40oC. Thermodynamic studies on lipase deactivation exhibited a first-order kinetic pattern. The activation and deactivation energies were 39.63 kJ/mol and 54.90 kJ/mol, respectively. The enthalpy and entropy of the lipase deactivation were found to be 52.12 kJ/mol and -0.18 kJ/mol, respectively.